2011
DOI: 10.1177/1461444811405020
|View full text |Cite
|
Sign up to set email alerts
|

YouTube interactions between agonism, antagonism and dialogue: Video responses to the anti-Islam filmFitna

Abstract: Fitna, is a 2008 short film made by a Dutch member of parliament to support his fight against Islam.It shows shocking footage of terrorism, violence and women's oppression and claims that these are inherent to Islam. The film caused immense controversy and mobilized people across the world to produce and upload their own views to YouTube. In this article we analyze these videos using different theoretical models of democratic interaction, and distinguishing between antagonism, 'agonism' and dialogue. On the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 17 publications
0
35
0
1
Order By: Relevance
“…Religious authorities can be unhelpful, and religious young people are sometimes withdrawn from school sex education by their parents. Nonetheless, respondents spoke positively about their faith as a resource -not least in response to highly sexualised wider British culture -and with peer support finding ways to negotiate between authority and experience (Page and Yip 2012;Yip, Keenan, and Page 2011).…”
Section: Religious Individualism and Decline In A Neoliberal Age?mentioning
confidence: 99%
“…Religious authorities can be unhelpful, and religious young people are sometimes withdrawn from school sex education by their parents. Nonetheless, respondents spoke positively about their faith as a resource -not least in response to highly sexualised wider British culture -and with peer support finding ways to negotiate between authority and experience (Page and Yip 2012;Yip, Keenan, and Page 2011).…”
Section: Religious Individualism and Decline In A Neoliberal Age?mentioning
confidence: 99%
“…The centrality of a few users in the YouTube-comments is a tendency that can also be observed on other social web-platforms (see for example: Bruns et al 2010;van Zoonen et al 2011), where a few core-participants dominate the discussion. The interpersonal communication in this example can also be seen as an example of what Bakardjieva (2009) describes as subactivism, individual encounters between citizens on digital media platforms that are part of the democratic potential of the Internet, but lack bridges to the public.…”
Section: Form and Frequenciesmentioning
confidence: 58%
“…In webometrics, another kind of a problem was identified by Van Zoonen, Vis andMihelj (2011, p. 1298), who suggested that "cybermetric search and analytic instrument runs the risk of suggesting 'completeness'", but this completeness is "by definition temporal, and biased towards well-established and maintained websites".…”
Section: Discussionmentioning
confidence: 99%
“…Even if the same data source can be used, it is likely that the data provider has altered access conditions to the data. Another challenge is the need for further research into political and religious conflict, online interaction and gender (Van Zoonen, Vis & Mihelj, 2011).…”
Section: Discussionmentioning
confidence: 99%